2012
DOI: 10.2337/db11-1157
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 Diabetes Is Associated With Enterovirus Infection in Gut Mucosa

Abstract: Enterovirus infections have been linked to type 1 diabetes in several studies. Enteroviruses also have tropism to pancreatic islets and can cause β-cell damage in experimental models. Viral persistence has been suspected to be an important pathogenetic factor. This study evaluates whether gut mucosa is a reservoir for enterovirus persistence in type 1 diabetic patients. Small-bowel mucosal biopsy samples from 39 type 1 diabetic patients, 41 control subjects, and 40 celiac disease patients were analyzed for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
116
2
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 137 publications
(127 citation statements)
references
References 35 publications
(35 reference statements)
8
116
2
1
Order By: Relevance
“…A recent study on intrafamilial spread of EV infections reported that 20% of siblings of diabetic probands acquired type 1 diabetes with a latency of 3-25 months [19]. Evidence for this association is supported by detection of EVs in the blood [13,14,17,22], pancreas [15,[23][24][25][26] and gut mucosa [27] of patients with type 1 diabetes. Histopathologic evidence indicates that expression of enteroviral capsid protein VP1 in islet cells of patients with type 1 diabetes is related to induction of protein kinase R and downregulation of Mcl-1 [23,24].…”
Section: Introductionmentioning
confidence: 97%
“…A recent study on intrafamilial spread of EV infections reported that 20% of siblings of diabetic probands acquired type 1 diabetes with a latency of 3-25 months [19]. Evidence for this association is supported by detection of EVs in the blood [13,14,17,22], pancreas [15,[23][24][25][26] and gut mucosa [27] of patients with type 1 diabetes. Histopathologic evidence indicates that expression of enteroviral capsid protein VP1 in islet cells of patients with type 1 diabetes is related to induction of protein kinase R and downregulation of Mcl-1 [23,24].…”
Section: Introductionmentioning
confidence: 97%
“…Epidemiological studies have suggested that infections with enteroviruses, in particular those of the coxsackie B virus (CVB) serotypes, may be linked to islet autoimmunity and development of type 1 diabetes [1][2][3][4][5]. Other observations suggesting that infections with these viruses have a causative role in diabetes development come from studies that found enteroviruses more frequently in pancreases [6][7][8] and, in some studies, also gut biopsies [9][10][11], from patients with type 1 diabetes compared with healthy controls. Some enteroviruses, including the CVBs, are pancreatropic and can infect human beta cells in vitro, often with a detrimental outcome (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…EV infections are associated with the initiation of β cell destruction [10]. Evidence for this association has been supported by the detection of EVs in the blood [15], pancreas and islets [12], and gut mucosa [16] of patients with T1D. Our study indicated a prevalence of EV infection in the blood of T1D children is 26.2%.…”
Section: Discussionmentioning
confidence: 57%